앱 아이콘의 시각적 수사기법 응용 분석 - 중국 쇼트 비디오/라이브 앱을 중심으로 - 호위위; Hu Wei Wei; 박용진; Park Yong Jin (기초조형학연구, 2021)
현재 인터넷 기술이 빠르게 발전하는 환경에서 각종 쇼트 비디오/라이브 앱이 대량으로 등장하면서 갈수록 앱 아이콘 디자인의 동질화가 심화되고 있다. 본 연구의 목적은 쇼트 비디오/라이브 앱 아이콘의 디자인 요소와 시각적 수사기법에 대한 분석을 통해 앱 아이콘의 시각적 수사기법의 응용과 현재 앱 아이콘의 디자인 규칙을 고찰하며, 이를 통해 아이콘 디자인에 대한 다양한 사고를 제공하기 위한 것이다. 연구 방법은 앱 아이콘의 디자인 요소를 분석하고, 또한 쇼트 비디오/라이브 앱 아이콘에서 나타나는 시각적 수사기법에 대해 시각 디자인 전공자 5명의 설문 조사를 진행하여 이에 비유법 중 은유, 직유, 환유, 의인이 주로 표현된 시각적 수사기법을 도출한다. 디자인 요소와 시각적 수사기법의 두 가지 측면을 결합하여 앱 아이콘의 시각적 수사기법 응용과 시각 표현을 분석하였다. 연구 범위는 2020년 상반기 해외 앱스토어와 구글플레이 다운로드 순위 TOP20의 중국 쇼트 비디오/라이브 앱을 조사 대상으로 하였다. 연구 결과 쇼트 비디오/라이브 앱 아이콘은 특성에 따라 디자인 형식이 다르게 나타났다. 디자인 요소 중에서 쇼트 라이브 앱은 기하학 도형과 기능 도형에서 추출한 요소를 많이 사용하고, 라이브 앱은 동물 캐릭터 요소와 기능 도형에서 추출한 요소를 주로 사용하였다. 또한 시각적 수사기법의 관점에서 볼 때 쇼트 비디오 앱은 은유와 직유를 많이 사용하고, 라이브 앱은 의인화와 직유를 주로 사용하였다. 쇼트 비디오/라이브 앱 아이콘에서 발견된 공통점은 기능 도형에서 추출한 요소에 직유를 적용한 시각적 수사기법을 사용하고, 현재 범용성이 강한 아이콘이 주요 디자인 형식을 사용했다는 것이다. 차이점은 쇼트 비디오 앱은 주로 기하학 도형을 은유적으로 사용하여 아이콘을 디자인하고, 라이브 앱은 동물 캐릭터 아이콘을 의인화하여 해당 앱의 활력과 분위기를 전달한다는 것이다. As the internet technology is developing rapidly, various short videos/livestreaming APPs have appeared. Therefore, the homogenization of APP icon design is increasingly severe. The research purpose is to explore how to apply visual rhetorical devices of APP icons and visual presentation of the APP icon design, with the method of analyzing the design elements and visual rhetorical devices of short videos/livestreaming APP icons. It aims to provide multi-perspective thinking manners for icon design. The research method is to analyze the design elements of the APP icons and distribute questionnaires to five visual designers about the rhetorical device performance in short videos/livestreaming APP icons. It summarizes the main visual rhetorical devices (metaphor, simile, metonymy and personification) and combines two aspects (design element and visual rhetorical device) to analyze the application of visual rhetorical devices and visual performances of APP icons. The research scope is the top 20 short videos/livestreaming APP icons in the downloads of the foreign App Store and Google Play in China in the first half of 2020. Research results show that different APPs have different characteristics and the design forms are also different; among the design elements of short videos/livestreaming APP icons, most short video APPs extract geometric graphs and functional patterns. Most livestreaming APPs extract animal cartoons and functional patterns. In terms of visual rhetorical devices, most short video APPs use metaphors and similes; most livestreaming APPs use simile and personification. The similarity is that the extraction of functional patterns adopts the visual rhetorical device of simile; the general icon is the main design form of icons. The difference is that the short videos mainly metaphorically use geometric graphs, thus endowing the icon with a stronger sense of design. Livestreaming mainly uses the personified animal cartoon icons to show the vitality and atmosphere of the livestreaming APPs.